Building resilience against cholera: lessons from the implementation of integrated community strategy for cholera control in Zambia - Nyuma Mbewe; Fred Kapaya; Moses Mwale; Peter Jay Chipimo; Precious Kalubula; Ladislas Hibusu; Stella Mumba Chomba Mulima; Kafusha Kapema; Kelvin Mwangilwa (BMJ Global Health)
Cholera has remained a persistent public health challenge in Zambia since the country’s first reported outbreak in 1977. The recent outbreak, which began in October 2023 and is ongoing as of June 2024, is the most severe in Zambia’s history and part of the larger 2022–2024 Southern Africa cholera outbreak, which has affected multiple countries in the region. This article describes the implementation of the integrated community strategy for cholera control (ICSCC) in three districts of the Copperbelt Province during this outbreak. The ICSCC is a comprehensive, community-centric public health approach that integrates surveillance, case management, water, sanitation and hygiene interventions, community engagement and infection prevention measures. The strategy’s implementation involved deploying multidisciplinary technical teams, training community-based volunteers and healthcare workers in the affected communities. This approach led to a rapid reduction in cholera cases and mortality, largely due to enhanced surveillance, community education sessions and improved sanitation practices. The ICSCC also improved stakeholder coordination and enabled rapid communication for early response to cholera hotspots. Key lessons learnt include the importance of robust coordination, early community involvement and context-specific adaptations. The strategy’s emphasis on data-driven decision-making and adaptation to local socio-cultural dynamics was crucial for its effectiveness. These findings underscore the potential of integrated community-based approaches in managing cholera outbreaks, enhancing public health preparedness and building long-term resilience. The ICSCC strategy offers a scalable model for regions facing similar public health challenges, providing valuable insights for policymakers and practitioners on the effectiveness of community involvement in managing public health crises.